2004
DOI: 10.1159/000082038
|View full text |Cite
|
Sign up to set email alerts
|

Central Representation of Somatic Sensations in the Parietal Operculum (SII) and Insula

Abstract: Four subjects with small restricted cerebral cortical infarcts have been examined. One had a lesion confined to the parietal operculum (SII), while in the second the SII lesion also encroached on the posterior insula; in the third subject, both banks of the sylvian fissure and the dorsal insula were involved, while in the fourth the lesion involved the upper bank of the sylvian fissure. In all cases, the postcentral gyrus (SI) was intact. Subjects 1 and 2 had mild spontaneous pain, but subjects 3 and 4 had nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…We have previously suggested that the presence of spontaneous central pain alters cortical mechanisms for the perception of thermal sensations [14]. Here we present further evidence from the 4 patients described in that publication and add data from 2 additional patients.…”
Section: Introductionsupporting
confidence: 53%
“…We have previously suggested that the presence of spontaneous central pain alters cortical mechanisms for the perception of thermal sensations [14]. Here we present further evidence from the 4 patients described in that publication and add data from 2 additional patients.…”
Section: Introductionsupporting
confidence: 53%
“…Electrical stimulation of the dpIns in awake humans can result in specific thermal sensations (39). A laser-evoked potential study provided evidence that selective warming specifically activates the dpIns (29), and recent fMRI studies provided supplemental data supporting activation of the insular cortex by cooling and "paradoxical heat" (3,18,20). Notably, imaging evidence also indicates strong activation of the human dpIns by noxious cold (8,12,36).…”
Section: Discussionmentioning
confidence: 99%
“…It incorporates anatomic findings indicating that the dpIns has a major role in the control of homeostatic integration, including direct projections to critical sites in the brain stem. A cardinal (and nearly universal) feature of this syndrome is that such burning pain occurs in the region of the body where the thermosensory dysfunction is most profound (3,16). In order for this cross-modal topographic correspondence to occur, the thermosensory representation in the dpIns (and its forebrain and descending connections) must be somatotopically organized.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that electrical stimulation in and around the insula produces perception of pain (Afif et al, 2008;Frot and Mauguiere, 2003;Ostrowsky et al, 2002) in the same manner that lesions do e.g. after a stroke involving the operculo-insula region (Bowsher et al, 2004). Despite extensive insular lesions, these patients retained the ability to discriminate between different degrees of evoked pain intensity but with overall increased intensity ratings (Starr et al, 2009).…”
Section: Introductionmentioning
confidence: 87%